Effect of Work Environment and Work Stress on Employee Performance - Mailani Rabiulkhri; Tati Herlina; Nourma Wulandari; Riki Adriant; Muhammad Rizki Romadhon (Politeknik Negeri Sriwijaya, 2022)
The data analysis technique used is Multiple Linear Regression. Based on the results of the partial analysis there is a significant effect of the work environment on employee performance at PT. Baturaja Cellular Multi Media with a t value of 3,413. Work stress variable has a significant effect on employee performance at PT. Baturaja Cellular Multi Media with a t value of 5,108. Simultaneously, it was found that there was an effect of work environment and work stress on employee performance at PT. Baturaja Cellular Multi Media with a calculated F value of 58,675. The coefficient of determination (R2) obtained is 0.741. This shows that the contribution of the influence of the work environment and work stress on employee performance is 74.1% while the remaining 25.9% is influenced by other variables not mentioned in this study such as intellectual ability, work discipline, job satisfaction, and employee motivation.